PYXIDA - Mourikis, Antonios; Kapetis, Chrysostomos (Qualitative and Quantitative Methods in Libraries, 2019)
The present paper serves as a case study which demonstrates the project of implementation of the Institutional Repository by the AUEB’s Library. The project was co-funded by the EU and the Greek government in the framework of a broader program of digitization. The paper describes the main stages of the creation and implementation of the repository including the adoption of a digital repository system, the digitization of selected printed items, the documentation of the digitized material and the definition of deposition policies. The ultimate purpose of this article is to highlight the crucial factors for the successful implementation of the repository so as to serve as an added value for the University.